PERFORMANCE OF BROILER WERE GIVEN TURMERIC (Curcuma domestica Val.) AND TAMARIND (Tamarindus indica L.) ON DRINKING WATER - N. P. K., WARDANI,; DEWI, G. A. M. K.; CANDRAWATI, D. P. M. A. (Majalah Ilmiah Peternakan, 2022)
This experiment was conducted to find out performance of broiler was given turmeric, tamarind, and mixed turmeric and tamarind on drinking water used Completely Randomized Design (CRD) consisting of 4 treatments dan 5 replications. The treatments are given without turmeric and tamarind (A), 2% turmeric (B), 2% tamarind (C), and mixed 1% turmeric and 1% tamarind (D). The observed variables are initial body weight, final body weight, daily body weight, feed consumption, water comsuption, and FCR. The results indicated that was given 2% turmeric (B), 2% tamarind (C) and mixed 1% turmeric and 1% tamarind (D) significantly increased (P<0,05) of final body weigth, daily body weight, water comsuption, and FCR but different significantly (P>0,05) of feed comsuption compared to the control (A). Based on concluded that was given 2% turmeric (B), 2% tamarind (C) and mixed of 1% turmeric and 1% tamarind (D) on water drinking able to provide the same ration consumption, but can increased of final body weight, daily body weight and efficient in untilizing rations while broiler was given mixed 1% turmeric and 1% tamarind (D) can increased water comsuption.